The Chinese-Kazakhstan relations in historical and political science Russia - Dosova, B.A. (Ye.A.Buketov Karaganda State University Publ., 2012)
The article is devoted to the analysis of Russian historical and political science literature on the problem of China’s Central Asian policy taking the example of the Chinese-Kazakhstan relations in the 1990–2000 ss. The author concludes that the Sino-Kazakh relations scholars are given a positive assessment, but a number of factors are named which can affect positive prospects of bilateral relationship.
Ресейдің тарихи жəне саяси əдебиетіндегі қытай-қазақстан қарым-қатынасы
Китайско-казахстанские отношения в исторической и политологической литературе России
Keywords: Russia; China; Central Asia; Kazakhstan; the Chinese-Kazakhstan relations; Russian historiography